Improved de novo Assembly of the Achlorophyllous Orchid Gastrodia elata - Chen, Shanshan; Wang, Xiao; Wang, Yangzi; Zhang, Guanghui; Song, Wanling; Dong, Xiao; Arnold, Michael L.; Wang, Wen; Miao, Jianhua; Chen, Wei; Dong, Yang (Frontiers in Genetics, 2020)
Achlorophyllous plants are full mycoheterotrophic plants with no chlorophyll and they obtain their nutrients from soil fungi. Gastrodia elata is a perennial, achlorophyllous orchid that displays distinctive evolutionary strategy of adaptation to the non-photosynthetic lifestyle. Here in this study, the genome of G. elata was assembled to 1.12 Gb with a contig N50 size of 110 kb and a scaffold N50 size of 1.64 Mb so that it helped unveil the genetic basics of those adaptive changes. Based on the genomic data, key genes related to photosynthesis, leaf development, and plastid division pathways were found to be lost or under relaxed selection during the course of evolution. Thus, the genome sequence of G. elata provides a good resource for future investigations of the evolution of orchids and other achlorophyllous plants.